Comparative Analysis of Root System Architectural Traits In Genotypes of Vigna Radiata L. And Vigna Mungo L. (Bangladesh Journal of Botany, 2023)
Investigation of root system architecture (RSA) has a huge potential to support the crop improvement under suboptimal nutrient and water conditions. The present study was carried out using eight genotypes of each mungbean and urdbean for comparative analysis of RSA traits among the genotypes. Presence of significant variations and medium to high heritability was observed for RSA traits. The genotypes KM 12-29 followed by PUSA 9072 among the mungbean genotypes and LBG 623 followed by PU 11-14 among the urdbean genotypes showed higher proportion of RSA traits. The higher percentage distribution of root traits was observed under diameter intervals in the order of 0-0.5 > 0.5-1.0 > 1.0-1.5 > 1.5-2.0 >> 2.0 mm in both mungbean and urdbean genotypes. Thus, the study shows the clear depiction and comparison of RSA traits among mungbean and urdbean genotypes, which can be exploited for cultivar development in future breeding programmes.Bangladesh J. Bot. 52(1): 61-69, 2023 (March)